(untitled) (Saúde Ética & Justiça, 2021)
Objective: Currently in Brazil, there is a recurring discussion about the decriminalization or not of voluntary termination of pregnancy. The present work conducted a Constitutional analysis on the theme and what fundamental principles criminalization would be going against. The study furthermore aimed to define abortion, how it is currently structured in the Brazilian legal system and the current possibilities of legal abortion in Brazil, as well as provide considerations on the creation of Ordinance No. 2.561/2020 and whether it violates fundamental rights of women. The study also presents an analysis of ADI 3.510, on the idea of a balance of rights between fetus and human being in the judiciary. Methods: The methodology used for the research was the bibliographic review on the subject and jurisprudential analysis. Conclusion: The study resulted in the unconstitutionality of the criminalization of voluntary termination of pregnancy, due to the violation of the principles of human dignity and autonomy of the will. The State cannot interfere in the woman's private and intimate decision.